2019
DOI: 10.15663/wje.v24i2.672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of school locality on teaching and learning: A qualitative inquiry

Abstract: This research examined the impact of school location on teaching and learning through a case study of two urban, two rural and two remote Fijian secondary schools. A total of 48 semi-structured interviews were conducted: 16 from each category of urban, rural and remote. Each school was represented by three teachers, three heads of department and two administrators. The study established that rural and remote schools often face different challenges to their urban counterparts: geography, poverty and funding inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…This finding differs from the study of Wang (2013), who found that compared to urban schools, remote schools have less access to technology and lower levels of computer literacy among instructors and students. In addition, unstable internet networks (Beng et al, 2018), as well as a lack of resources and infrastructure (Chand & Mohan. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This finding differs from the study of Wang (2013), who found that compared to urban schools, remote schools have less access to technology and lower levels of computer literacy among instructors and students. In addition, unstable internet networks (Beng et al, 2018), as well as a lack of resources and infrastructure (Chand & Mohan. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rural teachers revealed that factors out of their control (social and political) were far more prevalent stressors than personal factors (Randell, 2019), but compared to non-rural teachers, rural teachers were found to spend nearly an hour less each week (on average) communicating with colleagues (Woodland & Mazur, 2019). A study on Fijian schools found rurality affects cooperation in addition to the professional exchange of ideas with rural teachers having little time during or after school to dialogue (Chand & Mohan, 2019). This, in turn, affects teachers' professional growth and professional identity which together can increase teachers' feelings of burnout (Xu et al, 2023).…”
Section: Jiangang Xia and Sam Butlermentioning
confidence: 99%